2019
DOI: 10.1016/j.omtm.2019.01.010
|View full text |Cite
|
Sign up to set email alerts
|

EU Regulatory Pathways for ATMPs: Standard, Accelerated and Adaptive Pathways to Marketing Authorisation

Abstract: Advanced therapy medicinal products (ATMPs) require evaluation by the European Medicines Agency’s Committee for Advanced Therapies prior to being placed on the European market, subject to a Marketing Authorisation granted by the European Commission. In common with other medicinal products, various regulatory pathways are available for taking ATMPs through clinical trials to market authorisation, and the regulatory pathway taken will depend on a product’s characteristics and the target patient population. With … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 27 publications
0
98
0
4
Order By: Relevance
“…These trials are named confirmatory trials and they are performed in different hospitals to confirm and make a full characterization of the product's efficacy. 10,24 The cohort size number included in a clinical trial design for TBPs depends on the pathology to treat and the manufacturing capacity of the product. According to these considerations, any clinical trial phase should be designed with an adequate number of patients (both for the target population arm and for the control group arm) to obtain consistent and feasible clinical data.…”
Section: Development Stages Of a Tbpmentioning
confidence: 99%
See 1 more Smart Citation
“…These trials are named confirmatory trials and they are performed in different hospitals to confirm and make a full characterization of the product's efficacy. 10,24 The cohort size number included in a clinical trial design for TBPs depends on the pathology to treat and the manufacturing capacity of the product. According to these considerations, any clinical trial phase should be designed with an adequate number of patients (both for the target population arm and for the control group arm) to obtain consistent and feasible clinical data.…”
Section: Development Stages Of a Tbpmentioning
confidence: 99%
“…24 According to the extent of clinical data available, three types of MAAs can be granted in a centralized procedure for a TBP: (i) a standard MAA, when comprehensive clinical data can be provided; (ii) a conditional MAA, when comprehensive clinical data is not expected to be obtained, and in this case, the EMA may request additional postauthorization studies; or (iii) an exceptional circumstance MAA, when comprehensive clinical data can be obtained in time. 24 A granted standard MAA for a TBP (TEPs or CATMPs) is only valid for 5 years. Thereafter, the EC may renew the authorization indefinitely or decides not to validate it again.…”
Section: Regulatory Framework In the Eumentioning
confidence: 99%
“…Two independent studies demonstrated that a CAR-T cell with reduced affinity rendered T cells preferentially activated by a high, but not low, density of target antigen [112,113]. burdensome for academic institutions, although the new European clinical trial regulation favors accelerated novel drug evaluation and approval schemes to ensure early access to innovative therapies [114]. The majority of subjects treated to date with ATCT have received autologous or allogeneic dedicated T cells, but this approach may not be best suited for widespread cost-effective delivery of cellular therapy, since these are personalized medicines that are produced on-demand through a complex and costly supply chain, thus implying some delay in manufacturing of the final product and the risk that the disease will evolve and be fatal for candidate patients.…”
Section: Increasing T-cell Therapy Safetymentioning
confidence: 99%
“…However, to date there is still a lack of a widespread implementation of TE therapeutics in clinics with only four TE products having obtained to date official marketing authorisation in the EU. These are Spherox (CO.DON), Holoclar (Chiesi Farmaceutici), MACI (Vericel) and Chondrocelect (TiGenix), however, the last two products are no longer authorised or have been suspended [1]. This demonstrates that there is still considerable progress to be made before a systematic and consistent pipeline of TE products to the clinic can be established.…”
Section: Introductionmentioning
confidence: 99%